Analyzing the Impact of Voluntary Integrated Reporting on Investor Decisions: Investigating the Mediating Role of Information Asymmetry Reduction in Listed Companies on the Iraq Stock Exchange (Journal of Humanities and Social Sciences Research, 2023)
This study examines the influence of voluntary integrated reporting on investor decisions, specifically investigating the mediating role of information asymmetry reduction in listed companies on the Iraq Stock Exchange. The sample consists of 47 dealers from the Iraq Stock Exchange. Data collection involved the use of a questionnaire. Statistical analysis was conducted using SPSS and AMOS software, utilizing various statistical methods such as mean, standard deviation, Pearson correlation coefficient, and path analysis The most significant finding of this study suggests that voluntary integrated reporting plays a crucial role in reducing information asymmetry, thereby impacting investor decisions. The mediating role of information asymmetry reduction highlights the importance of transparent and comprehensive reporting practices in influencing investment behavior. These findings contribute to the understanding of the relationship between integrated reporting, information asymmetry, and investor decision-making in the context of the Iraq Stock Exchange.